Laparoscopic gastrectomy for early gastric cancer targeting as a less invasive procedure - Kawamura, Hideki; Okada, Kuniaki; Isizu, Hiroyuki; Masuko, Hiroyuki; Yamagami, Hideki; Honma, Shigenori; Ueki, Shinya; Noguchi, Keita; Kondo, Yukifumi (Surgical endoscopy, 2008)
Background Since only a few extensive reports are available on the less invasive nature of laparoscopic gastrectomy, we compared postoperative changes over time in vital signs and hematological parameters between this surgery and laparotomic gastrectomy. Methods Of 188 patients who underwent distal gastrectomy for preoperatively diagnosed early gastric cancer between January 2004 and September 2006, 87 underwent laparoscopy-assisted distal gastrectomy (LADG) and 101 underwent laparotomic distal gastrectomy (DG). The invasiveness of the two procedures was evaluated in 164 patients with no postoperative complications (82 cases of LADG and 82 cases of DG by measuing vital signs daily and performing hematological examination on postoperative days (POD) 1, 4, 7, and 10. Results For body temperature, heart rate, and blood pressure, significantly lower values were obtained with LADG on 3 and 4 POD, 4 POD, and 3 and 4 POD, respectively. For white blood cell counts (WBC) and C-reactive protein (CRP), significantly lower values were obtained with LADG on 7 and 10 POD, and 10 POD, respectively. For serum protein levels and lymphocyte counts, significantly higher values were obtained with LADG on 1, 4, 7, and 10 POD, and 4 and 10 POD, respectively. Body temperature, WBC, and CRP showed no significant difference immediately after surgery but earlier recovery occurred with LADG. For protein levels and lymphocyte counts, higher values were obtained immediately after surgery. There seemed to be two patterns of less invasiveness in the parameters: the early recovery found for body temperature, WBC and CRP, and the smaller shift immediately after surgery in protein level and lymphocyte count, and probably, heart rate and blood pressure. The complication rate was 18.8% for DG and 5.7% for LADG. Conclusions LADG is a less-invasive surgical procedure as it produces early normalization or smaller shifts in various parameters and exhibits a low prevalence of complications.